The effect of liver disease on hepatic microenvironment and implications for immune therapy - Zachary J. Brown; Samantha M. Ruff; Timothy M. Pawlik (Frontiers Media S.A., 2023)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer and the fourth leading cause of cancer-related death worldwide. HCC often occurs in the setting of chronic liver disease or cirrhosis. Recent evidence has highlighted the importance of the immune microenvironment in the development and progression of HCC, as well as its role in the potential response to therapy. Liver disease such as viral hepatitis, alcohol induced liver disease, and non-alcoholic fatty liver disease is a major risk factor for the development of HCC and has been demonstrated to alter the immune microenvironment. Alterations in the immune microenvironment may markedly influence the response to different therapeutic strategies. As such, research has focused on understanding the complex relationship among tumor cells, immune cells, and the surrounding liver parenchyma to treat HCC more effectively. We herein review the immune microenvironment, as well as the relative effect of liver disease on the immune microenvironment. In addition, we review how changes in the immune microenvironment can lead to therapeutic resistance, as well as highlight future strategies aimed at developing the next-generation of therapies for HCC.